Israel : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2008)
The methodologies used in this paper suggest that Israel's real exchange rate is moderately undervalued, while gains in external competitiveness appear to have been eroded in recent years. Market-based indicators provide a useful additional dimension to the analysis of financial stability in Israel. The Israeli government has made far-reaching reforms to financial markets in recent years. Banks' performance and financial strength have been improving. This paper proposes two rules that are based on a debt-brake concept and an alternative error-correction-mechanism toward fiscal policy in Israel.